The students' mathematics self-regulated learning and mathematics anxiety based on the use of chat GPT, music, study program, and academic achievement - Delima, Nita; Kusuma, Dianne Amor; Paulus, Erick (Jurnal Infinity, 2024)
In the era of society 5.0, the reach of student learning resources is increasingly wider, with the internet and free AI-based search engines. The use of music during learning is a way for students to increase learning motivation. This research aims to find out: (1) Whether ChatGPT technology and music used during independent study have an impact on students' Mathematics Self-Regulated Learning (MSRL) and Mathematics Anxiety (MA); (2) Whether MSRL and MA have an association with the study program students choose; and (3) Whether MSRL and MA have an association with students' academic achievement. This research uses a correlational descriptive research method. The data collection technique uses a survey, implementing Google Forms. The respondents of this research were students at several universities in Indonesia. The research results show a significant difference in MSRL between students who use ChatGPT and students who do not use ChatGPT during independent learning. However, there was no significant difference in MSRL between students who listened to music and those who did not listen to music during independent learning. There was no significant difference in MA between students who used ChatGPT and those who did not use ChatGPT during independent study. There was no significant difference in MA between students who listened to music and those who did not listen to music during independent study. There is a significant association between MSRL and the origin of the student's Study Program, but there is no significant association between MA and the origin of the Study Program. There is no significant association between MSRL and Academic Achievement. There is no association between MA and students' Academic Achievement.